Stara Ładoga w świetle ostatnich badań archeologicznych - Łosiński, Władysław (Polska Akademia Nauk. Instytut Historii Kultury Materialnej, 1981)
ill. ; 29 cm
Keywords: early Middle Ages -- Russia; archaeological research; history of Rus'; early medieval settlement; early medieval strongholds; Rus towns -- beginnings; early medieval economic and trade centres; early medieval economy; Staraya Ladoga (Russia)

Monety z imieniem Sieciecha : studjum z numizmatyki polskiej wieku XI - Majkowski, Edmund Klemens (1892–1951) (Polskie Towarzystwo Prehistoryczne, 1921)
ill. ; 29 cm
Keywords: Sieciech (c. XI / XII; palatine); 11 c. -- Poland; early medieval Polish coins; Sieciech's denarii; Sieciech's denarii -- iconography

Archeologia Polski. Vol. 15 (1970) No 2, Reviews and discussions - Leciejewicz, Lech (1931–2011). Reviewer (Zakład Narodowy im. Ossolińskich, 1970)
J. [Joachim] Herrmann, Siedlung, Wirtschaft und gesellschaftliche Verhältnisse der slawischen Stämme zwischen Oder/Neisse und Elbe, "Schriften der Sektion für Vor- und Frühgeschichte", Berlin, vol. 23 : 1968, 374 p., 45 drawings
P. 560-563 ; 25 cm
Bibliographical footnotes
Keywords: early Middle Ages -- Germany; Slavs (peoples); Slavs settlement -- Germany; early medieval economy; Oder/ Neisse and Elbe interfluve (Germany)

Archeologia Polski. Vol. 20 (1975) No 1, Reviews - Poklewski-Koziełł, Tadeusz (1932–2015). Reviewer (Zakład Narodowy im. Ossolińskich, 1975)
W. Łosiński, Początki wczesnośredniowiecznego osadnictwa grodowego w dorzeczu dolnej Parsęty (VII-X/XI w.), Wrocław-Warszawa-Kraków-Gdańsk 1972, Polska Akademia Nauk. Instytut Historii Kultury Materialnej
P. 214-219 ; 25 cm
Keywords: 7th-10th / 11th c. -- Poland; early medieval stronghold settlement -- Poland; early medieval defensive buildings; chronology of early medieval strongholds; spatial arrangement of early medieval strongholds; early medieval communities; early medieval tribal organization; early medieval economy; dating through pottery; Parsęta River valley (Poland)

Polska przed tysiącem lat - Hensel, Witold (1917–2008) (Zakł. Narodowy im. Ossolińskich, 1960)
Bibliogr.s.219-233
Polska Akademia Nauk. Instytut Historii Kultury Materialnej
232 s. : il. ; 24 cm
Keywords: Bronze Age-Iron Age -- Poland; early Middle Ages -- Poland; Proto-Slavs -- Poland; Polish state -- beginnings; state -- organization; early medieval settlement -- Poland; early medieval economy; early medieval art; cultural contacts in the early Middle Ages

Przemiany zasiedlenia na Wyżynie Głubczyckiej i w dorzeczu Liswarty w okresie lateńskim, rzymskim i początkach wczesnego średniowiecza - Godłowski, Kazimierz (1934–1995) (Zakład Narodowy im. Ossolińskich, 1980)
P. 131-166, [1] folded leaf : ill. ; 25 cm
German summary
Bibliography p. 158-162
Keywords: La Tene period-early Middle Ages -- Poland; La Tene period-early medieval settlement -- Poland; Celtic settlement -- Poland; Przeworsk culture; Przeworsk culture settlement; Przeworsk culture cemeteries; Roman coins; Roman coins finds; palynology; Głubczycki Palteau (Poland); Liswarta River basin (Poland)

Rola kontaktów ze Skandynawią w dziejach gospodarczych Słowian nadbałtyckich - Łosiński, Władysław (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 1997)
The author attempts to evaluate the significance of trade in the history of contacts between Scandinavians and Western Slavs. Their beginning may be dated back to the Vendel period but only at the end of that period and at the beginning of the Viking period did the contacts become more intensive. The trade comprised both luxury goods and bulk products and it centred in the manufacturing - trading open settlements. On the Slavic coast the newcomers from Scandinavia occupied the prominent position among the inhabitants of the settlements. The role of the Slavic element became more prominent in the late 9th cent. with thedevelopment of early towns, which became the centres of economic and social - political life of tribal communities. Further intensification of trade occurred in the late 10th cent., when the early-Piast monarchy entered the sphere of influence of the Baltic economic zone
29 cm
Keywords: Baltic Slavs and Scandinavians -- role of trade; Slavs; Scandinavian peoples; Slavic Lands and Scandinavia -- contacts; Slavic-Scandinavian relations; Slavic economy; early medieval trade

Wczesnośredniowieczny przełom gospodarczy w Wielkopolsce oraz jego konsekwencje krajobrazowe i demograficzne - Kurnatowski, Stanisław (1929– ) (Zakład Narodowy im. Ossolińskich, 1975)
P. 145-160 : ill., diagrams ; 25 cm
Bibliographical footnotes
English summary
Keywords: early Middle Ages -- Poland; early medieval rural economy; natural environment and settlement; settlement processes -- population regions; demographic changes; Wielkopolska (Poland)

Szeligi pod Płockiem na początku wczesnego średniowiecza : zespół osadniczy z VI-VII w. - Szymański, Wojciech (1932– ) (Zakład Narodowy im. Ossolińskich ;, 1967)
Doctoral thesis (version). Institute of the History of Material Culture. Polish Academy of Sciences, 1964
Bibliographical footnotes
397 pp., 1 leaf of plates : ill., err. ; 24 cm + [5] leaves of plates
English summary
Keywords: early Middle Ages -- Poland; reports of archaeological works -- Poland; regional geographical environment -- Poland; history of material culture; early medieval communities; early medieval crafts; early medieval economy; spatial organization of early medieval settlements; archaeozoological analysis; metallurgical analysis; paleobotanical analysis; review of archaeological finds; Szeligi, Słupno commune (Poland)

Eksploatacja zasobów leśnych w rejonie Kruszwicy we wczesnym średniowieczu - Dzieduszycki, Wojciech (1946– ) (Zakład Narodowy im. Ossolińskich, 1977)
P. 137-169, [1] folded leaf : ill., maps, diagrams ; 25 cm
Bibliographical footnotes
German summary
Keywords: early Middle Ages -- Poland; dendrochronology; early medieval forest economy; forest resources in the early Middle Ages; forest resources in the early Middle Ages -- exploitation; forest resources - raw material; Kruszwica, district Inowrocław-region (Poland)

Annali della zecca di Roma. [6], Alessandro VI (1492-1503), Pio III (1503), Giulio II (1503-1513) - Martinori, Edoardo (1854–1935) (Istituto Italiano di Numismatica, 1918)
92 p. : ill. ; 25 cm
Index
Bibliography p. 87
Keywords: 15th -16th c. -- Italy; mint (Rome, Italy); late medieval-early modern papal coins; late medieval-early modern Italian coinage

Archeologia Polski T. 32 (1987) Z. 1, Recenzje - Dulinicz, Marek (1957–2010). Reviewer (Zakład Narodowy im. Ossolińskich, 1987)
Produktivkräfte und Produktionsverhältnisse in ur- und frühgeschichtlicher Zeit, F. Horst, B. Krüger red., Berlin 1985, ss. 356, 103 ryciny w tekście
P. 209-217 ; 25 cm
Bibliographical footnotes
Keywords: Tagung der Fachgruppe Ur- und Frühgeschichte (11; 1981; Berlin); Paleolithic-early Middle Ages -- Europe; conference (Berlin, Germany; 1981); settlement researches; Paleolithic-early medieval economy; natural environment and economy; Bronze Age-Iron Age metallurgy; Iron Age mineral resources; late Roman period-early medieval pottery (craft); animal breeding in early Middle Ages